A place in the shade : the new landscape & other essays - Correa, Charles, 1930-2015 (Hatje/Cantz, 2012)
Over the last fifty years, Charles Correa (b. 1930 in Secunderabad), has been of decisive importance to architecture in post-Independence India. He has also been a pioneer in addressing crucial issues of housing and urbanisation in the Third World, including the proliferation of squatters. This selection of essays and lectures covers a wide spectrum of themes, from the metaphysical to the pragmatic, on a variety of subjects - including architecture, urban planning, landscape, and individuals as diverse as Corbusier, Brunel and Mahatma Gandhi. Also incorporated is a reprint of his seminal 1985 book, long out of print, on Third World urbanisation 'The New Landscape'. Correa has won the highest honours of his profession, including the Gold Medals of the RIBA, the UIA and the IIA, as well as the Aga Khan Award for Architecture, and the Praemium Imperiale of Japan.